2022
DOI: 10.1080/13880209.2022.2074053
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on antiviral constituents in traditional Chinese medicines and their mechanisms of action

Abstract: Context Viruses have the characteristics of rapid transmission and high mortality. At present, western medicines still lack an ideal antiviral. As natural products, many traditional Chinese medicines (TCM) have certain inhibitory effects on viruses, which has become the hotspot of medical research in recent years. Objective The antiviral active ingredients and mechanisms of TCM against viral diseases was studied in combination with the pathogenesis of viral diseases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 213 publications
0
9
0
Order By: Relevance
“…Therefore, there is an urgent need to develop effective antiviral drugs to assist the vaccine. Many studies have shown that TCM has been used as a potential source for developing new drugs for treating viral infections due to their properties, such as few adverse effects, high availability, and low cost [ 45 46 ]. Several natural constituents of TCM, including tomatidine, octyl gallate, buddlejasaponin IVb, and quercetin, have been shown to possess anti-PEDV activity [ 2 10 40 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is an urgent need to develop effective antiviral drugs to assist the vaccine. Many studies have shown that TCM has been used as a potential source for developing new drugs for treating viral infections due to their properties, such as few adverse effects, high availability, and low cost [ 45 46 ]. Several natural constituents of TCM, including tomatidine, octyl gallate, buddlejasaponin IVb, and quercetin, have been shown to possess anti-PEDV activity [ 2 10 40 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the phytochemical constituent mechanisms of action in pharmacology is crucial before developing drugs from O. basilicum L. [ 88 ]. The antiviral properties of phytochemicals have been subject of substantial research in recent years, even after the world experienced a worldwide pandemic [ 89 ]. Therefore, it is crucial to maintain and expand this research into their antiviral properties in light of ongoing global health challenges.…”
Section: Antimicrobial Activities and Biomedical Usesmentioning
confidence: 99%
“…Unlike other drugs, TCM formulas have multiple targets, low toxicity, and strong regulatory effects. Therefore, they have attracted increasing attention [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other drugs, TCM formulas have multiple targets, low toxicity, and strong regulatory e ects. erefore, they have attracted increasing attention [7,8]. Zhinao capsule (ZNC), a Chinese patent medicine, is mainly composed of Dangshen (DS, Codonopsis pilosula), Huangqi (HQ, Astragali membranaceus), Huangjing (HJ, Polygonatum sibiricum), Rou Congrong (RCR, Cistanche deserticola), Yujin (YJ, Curcuma wenyujin), Shi Changpu (SCP, Acorus tatarinowii), Chuanxiong (CX, Ligusticum chuanxiong), and Dilong (DL, Pheretima aspergillum) and has good efficacy in treating AD [9].…”
Section: Introductionmentioning
confidence: 99%